Analysis of Judge's Consideration in Applying the Principles of Contract Law and Nebis in idem in the Examination of Civil Disputes Related to the Birth of an Agreement (Case Study of Case No. 969/Pdt.G/2022/PN.Tng. and No. 173/Pdt/2023/PT.BTN.) - Esti Ayu Hutami; Mohammad Saleh (LPPM Universitas Ekasakti Padang, 2024)
This study aims to explore the considerations made by judges of the Banten High Court in resolving Civil Case Number 173/Pdt./2023/PN.BTN. concerning a dispute over the sale and purchase of land, which involves marital property and is linked to the principles of nebis in idem and the fundamental theory of contract formation. The methodology involves inventorying primary and secondary legal materials related to land law, followed by the identification of these materials according to the central issues of the research. Through analysis of these legal materials, the researcher seeks to provide insights and solutions to the questions raised. The findings revealed that the judges of the High Court of Banten affirmed the decision of the Tangerang District Court in Civil Dispute Number 173/Pdt./2023/ PT.BTN. They found that the reasons behind the initial decision were correct, especially regarding the land and building ownership issue involving Mr. Arhan. Hence, it is crucial for judges to thoroughly review all aspects of a case, particularly the subject matter, to ensure a fair and just outcome that benefits all parties involved.